Projected Savings Associated with Lowering the Risk of Total Hip Arthroplasty Revision Due to Dislocation in Patients with Spinopelvic Pathology - Ackerman SJ; Vigdorchik JM; Siljander BR; Gililland JM; Sculco PK; Polly DW (Dove Medical Press, 2023)
Stacey J Ackerman,1 Jonathan M Vigdorchik,2 Breana R Siljander,2,3 Jeremy M Gililland,4 Peter K Sculco,2 David W Polly3 1Department of Biomedical Engineering, Johns Hopkins University, San Diego, CA, USA; 2Department of Orthopedic Surgery, Hospital for Special Surgery, New York, NY, USA; 3Department of Orthopedic Surgery, University of Minnesota, Minneapolis, MN, USA; 4Department of Orthopedic Surgery, University of Utah, Salt Lake City, UT, USACorrespondence: Stacey J Ackerman, Email stacey.ackerman.2019@gmail.comPurpose: In the United States (US), total hip arthroplasty (THA) is the most common hospital inpatient operation among Medicare beneficiaries and is ranked fourth when considering all payers. Spinopelvic pathology (SPP) is associated with an increased risk of THA revision (rTHA) due to dislocation. Several strategies have been proposed to mitigate the risk of instability in this population, including use of dual-mobility implants, anterior-based surgical approaches, and technology-assistance (digital 2D/3D pre-surgical planning, computer navigation, and robotic assistance). For primary THA (pTHA) patients with SPP who subsequently undergo rTHA due to dislocation, we aimed to estimate (1) target population size; (2) economic burden; and (3) 10-year projected savings to the US payer of lowering the risk of rTHA due to dislocation among pTHA patients with SPP.Methods: A budget impact analysis from the US payer perspective was undertaken using published literature; American Academy of Orthopaedic Surgeons American Joint Replacement Registry 2021 Annual Report; Centers for Medicare & Medicaid Services MEDPAR 2019; and National (Nationwide) Inpatient Sample (NIS) 2019. Expenditures were inflation-adjusted to 2021 US dollars using the Medical Care component of the Consumer Price Index. Sensitivity analyses were performed.Results: The target population size in 2021 was estimated at 5040 (range, 4830- 6309) for Medicare (fee-for-service plus Medicare Advantage) and 8003 (range, 7669- 10,018) for all-payer. Annual rTHA episode-of-care (through 90 days) expenditures for Medicare and all-payer were $185 million and $314 million, respectively. Using a 4.14% compound annual growth rate from NIS, the estimated number of applicable rTHA procedures that will be performed from 2022- 2031 was 63,419 Medicare and 100,697 all-payer. With each 10% reduction in relative risk of rTHA due to dislocation, Medicare and all-payer could save $233 million and $395 million, respectively, over a 10-year period.Conclusion: Among pTHA patients with spinopelvic pathology, a modest reduction in the risk of rTHA due to dislocation could achieve substantial cumulative savings to payers while improving healthcare quality.Keywords: total hip arthroplasty, revision, spinopelvic pathology, dislocation, economics